Proceedings of the Russian Conference on Digital Economy and Knowledge Management (RuDEcK 2020) 2020
DOI: 10.2991/aebmr.k.200730.083
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Modeling of the Diversified Rural Economy Development in the Context of Digitalization

Abstract: Currently, Russia's economy is undergoing a global transformation caused by digital technologies. The changes taking place contribute not only to favorable changes, but also entail the emergence of a number of potential risks and adverse consequences. Considering the most negative impact it has been revealed that the consequences can affect rural areas, whose economy is currently in need of the full support in connection with the diversified development path. The article presents the knowledge about the divers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Whereas Hulten showed that knowledge-related capital is an important source of economic growth in many developed countries, and it is positively related to the average per capita income [36], in Kenton, the knowledge economy is defined as a system based on intellectual capital with a large part of its economic value consisting of intangible assets such as the value of labor knowledge. Zakshevskii et al indicated that modern societies are facing a great challenge represented in their ability to reach the stage of the knowledge society, The progress and development of any society have become dependent on its ability to invest knowledge effectively, and this is achieved through the investment of education to apply scientific cognitive theories [45]. It was also defined as an economy in which the main components of economic growth depend on intellectual capabilities and not on material inputs and natural resources Gupte.…”
Section: The Concept and Measuring Of The Knowledge Economy (Ke)mentioning
confidence: 99%
“…Whereas Hulten showed that knowledge-related capital is an important source of economic growth in many developed countries, and it is positively related to the average per capita income [36], in Kenton, the knowledge economy is defined as a system based on intellectual capital with a large part of its economic value consisting of intangible assets such as the value of labor knowledge. Zakshevskii et al indicated that modern societies are facing a great challenge represented in their ability to reach the stage of the knowledge society, The progress and development of any society have become dependent on its ability to invest knowledge effectively, and this is achieved through the investment of education to apply scientific cognitive theories [45]. It was also defined as an economy in which the main components of economic growth depend on intellectual capabilities and not on material inputs and natural resources Gupte.…”
Section: The Concept and Measuring Of The Knowledge Economy (Ke)mentioning
confidence: 99%